Perception and knowledge of HPV-related and vaccine-related conditions among a large cohort of university students in Italy - T. Baldovin; C. Bertoncello; S. Cocchio; M. Fonzo; D. Gazzani; A. Buja; S. Majori; V. Baldo (Taylor & Francis Group, 2019)
HPV is involved in cervical, anal, penile, vulvar and oropharyngeal cancers, as well as genital warts. It is important to investigate knowledge and attitudes among university students, considering in this age a shift in healthcare decision-making from parents to students themselves. The aim of this study was to estimate knowledge and perception of HPV in terms of potential shame for HPV-related conditions, trust in vaccine efficacy and worry for potential side effects. The study involved students (18-25 years old) from the Universities of Padua and Verona, Italy. Socio-demographic and behavioural characteristics were collected with a questionnaire (n = 9988). Female gender and older age were positively associated with higher knowledge. The adjusted logistic regression showed an association between the set of perceptions investigated and the vaccination status, while a direct connection with knowledge was not found. However, another adjusted linear regression showed that a good set of perceptions could be partially explained by a high level of knowledge. Perceptions seem to fill an intermediate position between the knowledge and the decision to get vaccinated. The potential shame deriving from asking for HPV-vaccination was not identified as a relevant barrier. Having received information from healthcare workers, family and school showed to be positively associated with the adhesion to the vaccination policy. This study identifies university students as a possible target for HPV vaccination and pinpoints specific areas that might be targeted as first to encourage vaccine uptake. Primary prevention together with screening programmes remains essential in further reducing the burden of HPV-related diseases.